The prevalence of deep Venous thrombosis of the lower extremity in hospitalized bedridden orthopaedic patients: a pilot study - kumar, jagdesh; Badaruddin Sahito, Badaruddin Sahito; Muhammmad Soughat Katto; Nusrat Rasheed; Asif Ali Jatoi; Awais Abro (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the prevalence of objectively confirmed deep vein thrombosis of lower extremities in bedridden hospitalised orthopaedic patients who received no thromboprophylaxis. Method: The prospective cross-sectional study was conducted at Dr Ruth Pfau Civil Hospital, Karachi, from April to June 2021, and included all patients aged 40 years admitted for intended major lower limb surgery and expected to be confined to the bed for at least 4 days. Duplex ultrasound scanning of both legs was used to confirm deep vein thrombosis. Data was analysed using SPSS 22. Results: Of the 104 subjects, 60(57.6%) were males and 44(42.3%) were females. The overall mean age was 51.9±7.4 years. The most common type of fracture was the neck of femur 28(26.9%). The mean delay between the fracture and admission was 6.44±4.9 days. The mean length of hospital stay was 12.76±3.8 days. The overall prevalence of deep vein thrombosis was 16(15.3% and none of these patients had any symptom at all. Conclusion: There was 15.3% prevalence of deep vein thrombosis. Considering that the condition is potentially lethal, routine prophylaxis for all at-risk patients should be encouraged. Key Words: Prevalence, Deep venous thrombosis, Lower extremity, Orthopaedic patients.